Field based and laboratory data of sediment cores from the Lower Havel Inner Delta near Lake Gülpe, Brandenburg (Germany) - Anne Köhler; Marie Kaniecki; Birgit Schneider; Christoph Zielhofer (PANGAEA, 2025)
Sediment cores were recovered using a hand-held Cobra Pro (Atlas Copco) core drilling system with a 60 mm diameter open corer. One-meter segments were retrieved and assessed in the field for sedimentological features, including estimations of grain size, carbonate content, humus content, and redox features (AG Boden 2005, 2024). Colour descriptions were carried out using the Munsell Soil Color Chart. The exact positions of the drilling points were recorded using a differential GPS device (TOPCON HiPer II). The cores were photographed, documented and sampled at 5–10 cm intervals for subsequent laboratory analyses. Bulk samples from five selected cores (RK1, RK3, RK13, RK15, RK17) were freeze-dried, sieved (2 mm), and weighed. Total carbon (TC), total nitrogen (TN), and total sulfur (TS) contents were measured using a CNS analyzer (Vario EL cube, Elementar). Inorganic carbon (TIC) was determined using calcimeter measurements (Scheibler method, Eijkelkamp). Organic carbon (TOC) was calculated as TOC = TC - TIC. For the grain size analyses, sediment samples were first sieved to <2 mm and subsamples of 10 g were treated with 50 ml of 35% hydrogen peroxide (H?O?) and gently heated to remove organic matter. Following this, 10 ml of 0.4 N sodium pyrophosphate solution (Na?P?O?) was added to disperse the particles, and the suspension was subjected to ultrasonic treatment for 45 minutes. The sand fraction was analysed by dry sieving and classified into four size classes: coarse sand (2000–630 μm), medium sand (630–200 μm), fine sand (200–125 μm), and very fine sand (125–63 μm). Finer fractions were determined using X-ray granulometry (XRG) with a SediGraph III 5120 (Micromeritics). These included coarse silt (63–20 μm), medium silt (20–6.3 μm), fine silt (6.3–2.0 μm), coarse clay (2.0–0.6 μm), medium clay (0.6–0.2 μm), and fine clay (<0.2 μm).
In: Köhler, Anne; Pohle, Marco; Bauckholt, Matteo; Birnstengel, Susann; Kaniecki, Marie; Schneider, Birgit; Werban, Ulrike; Zielhofer, Christoph (2025): Geophysical, Sedimentological and Geochemical Data from the Lower Havel Inner Delta (Gülpe Island), Brandenburg (Germany) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.983208